A Qualitative Examination of VA Chaplains' Understandings and Interventions Related to Moral Injury in Military Veterans - Drescher, Kent D. (Journal of religion and health, 2018)
This study examines VA chaplains' understandings of moral injury (MI) and preferred intervention strategies. Drawing qualitative responses with a nationally-representative sample, content analyses indicated that chaplains' definitions of MI comprised three higher order clusters: (1) MI events, (2) mechanisms in development of MI, and (3) warning signs of MI. Similarly, chaplains' intervention foci could be grouped into three categories: (1) pastoral/therapeutic presence, (2) implementing specific interventions, and (3) therapeutic processes to promote moral repair. Findings are discussed related to emerging conceptualizations of MI, efforts to adapt existing evidence-based interventions to better address MI, and the potential benefits of better integrating chaplains into VA mental health service delivery.